Corporate Social Responsibility: An Assessment of the Enlightened Self-Interest Model - Keim, Gerald D. (Academy of Management Review, 1978)
Much recent discussion of corporate social responsibility has concerned operationality. Many activities subsumed under corporate social responsibility can be shown to be public or partially public goods. The theory of public goods can clarify and explain some complex problems of operationalizing the social responsibility doctrine. An examination of philanthropy provides some behavioral applications.